Pharmacogenetics- Strengthening the Clinical Medicine - Farhat, Kulsoom (Pakistan Armed Forces Medical Journal, 2022)
With a lengthy and wide-ranging history of Pharmacogenetics, the researchers to this date are still discovering more and more about how the genetic variability of individuals affect the response to the drugs. The terminology of pharmacogenetics was not introduced until 1957. How an individual’s genetic makeup affects his response to drugs is an emerging field which helps in predicting about the effectiveness of the drug for that particular individual. This field is growing day by day, which is helping the world develop effective and safe drugs.